From Systemic Banking Crises to Fiscal Costs : Risk Factors - Amaglobeli, David (IMF Working Papers; Working Paper ;, 2015)
This paper examines the risk factors associated with fiscal costs of systemic banking crises using cross-country data. We differentiate between immediate direct fiscal costs of government intervention (e.g., recapitalization and asset purchases) and overall fiscal costs of banking crises as proxied by changes in the public debt-to-GDP ratio. We find that both direct and overall fiscal costs of banking crises are high when countries enter the crisis with large banking sectors that rely on external funding, have leveraged non-financial private sectors, and use guarantees on bank liabilities during the crisis. The better quality of banking supervision and the higher coverage of deposit insurance help, however, alleviate the direct fiscal costs. We also identify a possible policy trade-off: costly short-term interventions are not necessarily associated with larger increases in public debt, supporting the thesis that immediate intervention may be actually cost-effective over time.